Viral metagenomics unveils MW (Malawi) polyomavirus infection in Brazilian pediatric patients with acute respiratory disease. Issue 4 (31st March 2023) - da Silva, Anielly S.; de Campos, Gabriel Montenegro; Giovanetti, Marta; Zucherato, Victória Simonatto; Lima, Alex Ranieri Jerônimo; Santos, Elaine Vieira; Haddad, Rodrigo; Ciccozzi, Massimo; Carlos Júnior Alcantara, Luiz; Elias, Maria Carolina; Sampaio, Sandra Coccuzzo; Covas, Dimas Tadeu; et al.
Abstract: Viral metagenomics has been extensively applied for the identification of emerging or poorly characterized viruses. In this study, we applied metagenomics for the identification of viral infections among pediatric patients with acute respiratory disease, but who tested negative for SARS‐CoV‐2. Twelve pools composed of eight nasopharyngeal specimens were submitted to viral metagenomics. Surprisingly, in two of the pools, we identified reads belonging to the poorly characterized Malawi polyomavirus (MWPyV). Then, the samples composing the positive pools were individually tested using quantitative polymerase chain reaction for identification of the MWPyV index cases. MWPyV‐positive samples were also submitted to respiratory virus panel testing due to the metagenomic identification of different clinically important viruses. Of note, MWPyV‐positive samples tested also positive for respiratory syncytial virus types A and B. In this study, we retrieved two complete MWPyV genome sequences from the index samples that were submitted to phylogenetic inference to investigate their viral origin. Our study represents the first molecular and genomic characterization of MWPyV obtained from pediatric patients in South America. The detection of MWPyV in acutely infected infants suggests that this virus might participate (coparticipate) in cases of respiratory symptoms. Nevertheless, future studies based on testing of a larger number of clinical samples and MWPyV complete genomes appear to be necessary to elucidate if this emerging polyomavirus might be clinically important.